Avaliação da qualidade pós-colheita de mirtilo Bluegem sob atmosfera controlada e tangerina Ponkan sob atmosfera modificada em armazenamento refrigerado - Galarça, Simone Padilha (2009)
The objective of the present work was to evaluate the sensory and physical-chemical characteristics of organic blueberry ‗Bluegem and tangerine ‗Ponkan fruits, submitted to controlled or modified atmosphere, respectively. Also, it was tested the use of two concentrations of propolis as fruit coating of the citrus. Therefore, the blueberries ‗Bluegem (2007) and tangerines ‗Ponkan (2008) were harvested at the consumption stage. Then, the fruits were selected and storage after treatment. ‗Bluegem was stored at 1.5ºC with relative humidity (RH) of 90-95% and submitted to the following treatments: control 21KPa O2 + 0.03KPa CO2 (T1 - natural atmosphere), 4KPa O2 + 5KPa CO2 (T2) or 4KPa O2 + 10KPa CO2 (T3). The fruits were kept under storage for a period of 14 (P1), 28 (P2) or 42 (P3) days at 1.5°C, plus one day of simulated commercialization at 20°C and 70-75% RH. ‗Ponkan was stored at 4°C and 90-95%RH. The fruits were treated with: no wax (T1); ‗Carnaúba -based wax, 18% (T2); extract of propolis, 100% (T3) or extract of propolis, 90% + soybean oil, 10% (T4). Each fruit was individually treated with 0.25mL of the product. Subsequently, fruits were stored for a period of 15 (P1), 30 (P2) or 45 (P3) days plus three days of simulated commercialization at 15°C and 70-75% RH. A completely randomized design was used for the physical-chemical analysis, and for the sensory analysis a randomized block design; each judger was considered as a replication. Data were submitted to analysis of variance, and for mean comparison it was applied the Tukey test at 5% of error probability. The Pearson correlation was also carried between the physical-chemical and sensory variables. Blueberries ‗Bluegem can be stored up to 28 days at 1.5ºC plus one day of simulated commercialization at 20°C to keep their quality, whether treated with 5 or 10KPa CO2 and 4KPa O2. Using cold storage fruits could be stored up to 14 days at 1.5°C plus one day of simulated commercialization at 20°C, without compromising the quality of in natura consumption. Tangerines kept for 30 days at 90-95%RH and 4ºC suffered depreciation due to physiological disturbs. The essence of propolis reduced mass loss; however, whether added soybean oil it conferred slighter brightness to the fruit. ‗Carnaúba -based oil provide brighter fruits. According results, changing in the atmosphere of the storage environment (either controlled or modified storage) optimizes the storage of blueberries ‗Bluegem and tangerines ‗Ponkan , delaying senescence and keeping quality (support: CAPES).